2021
DOI: 10.1021/acsanm.1c00122
|View full text |Cite
|
Sign up to set email alerts
|

MoS2Nanosheet-Modified NiO Layers on a Conducting Carbon Paper for Glucose Sensing

Abstract: In this research, we demonstrate a disposable carbon-based paper electrode with engineered surfaces that is capable of detecting glucose in an alkaline medium at concentrations down to 10 μM. The sensitive electrode is fabricated by introducing a hydrothermally synthesized nickel oxide (NiO) layer on a carbon paper electrode, followed by the growth of nanostructured molybdenum disulfide (MoS 2 ) by pulsed laser deposition on the NiO layer. The surface modification was investigated using transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In the process, the fabricated organic composite electrodes were prone to breaking due to their fragileness. 39 Also, the sensitivity and detection limit of available paper electrodes to glucose 1,[40][41][42][43][44][45][46][47][48] still need to be further improved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the process, the fabricated organic composite electrodes were prone to breaking due to their fragileness. 39 Also, the sensitivity and detection limit of available paper electrodes to glucose 1,[40][41][42][43][44][45][46][47][48] still need to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon indicated that the hydrophilic side of the paper electrode was critical to the glucose detection, in agreement with the previous reports. [40][41][42][43][46][47][48]76,77 Possible reasons could be ascribed to the fact that glucose is a polar molecule and has more tendency to adsorb on the hydrophilic back side of the electrode relative to the hydrophobic front side. When the hydrophilic side was shielded with hydrophobic adhesive tape, the possibility of adsorbing glucose on the electrode became low, thus leading to a poor electrochemical performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical biosensors have been considered as a particularly promising class owing to their exceptional performances include high sensitivity and selectivity, rapid response, low cost, simple instrumentation, easy miniaturization and good quantitative ability. [12][13][14][15] In particular, nanomaterials with unique electronic, catalytic properties, good stability and large specific surface area play key roles. [16,17] TMDs are good candidates of them ascribed to their outstanding physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies showed that emergent materials could show enough sensitivity to glucose, there is an increasing interest in the fabrication of low-cost electrodes using transition metals such as copper , and nickel and transition metal oxides such as copper oxide, titanium oxide, nickel oxide, and cobalt oxide to construct nonenzymatic glucose biosensors. The properties of nonenzymatic sensors such as sensitivity, detection limit, response time, selectivity, and stability highly depend on the types and morphology of the materials. The performance of the nonenzymatic sensors may be increased using different nanostructures like Pt–Pb alloy, Pt–Au alloy, Pt/Au surface, Ag–Pt core–shell NWs, Ni–Cu alloy, and Pt–Ag/Cu alloy .…”
Section: Introductionmentioning
confidence: 99%